The Dynamics of the Melengkan Tradition as the Islamic Cultural Heritage of the Gayo Ethnic Community in Kuning II Village - Novia Astari; Nabila Yasmin (Medan Resource Center, 2026)
Melengkan is one of the oral traditions that has long been preserved by the Gayo community in Aceh and represents an important form of Islamic cultural heritage embedded in customary life. This study investigates the historical development of the Melengkan tradition, its functions and position in Gayo society, its implementation process, its relationship with Islamic values, and the socio-cultural dynamics influencing its continuity. This research employs a qualitative method using a socio-historical approach. Data were collected through interviews, observation, documentation, and literature studies. The primary informants were Ramli, a traditional elder of Kuning II Village, and Adan, a Melengkan practitioner actively involved in customary ceremonies. The findings demonstrate that Melengkan has continuously adapted to changing social conditions while maintaining its essential role as a medium of customary communication, cultural education, social integration, and the transmission of Islamic moral values. The study highlights the novelty that Melengkan's sustainability is shaped by the interaction among cultural preservation, Islamic value integration, and community adaptation to contemporary social change. These findings contribute to socio-cultural and historical studies by illustrating how local traditions remain relevant through cultural adaptation and provide practical insights for strengthening the preservation of Gayo cultural heritage.